Dynamic service orchestration in the IP multimedia subsystem - Spiers, Richard (Department of Electrical Engineering, 2017)
The continued growth of the Internet has resulted in a massive uptake of different communication services. An ever-increasing number of users are utilising rich multimedia services, and are both consuming and producing user generated content. This rapid growth in bandwidth and complexity has resulted in challenges for the previous architectures used in telecommunication networks. As a result, two of the major challenges faced by telecommunication network operators are an increase in the number of services that an end user expects to be able to use, as well as the desire to have personalised, custom use of these services. Over-the-top providers have begun to offer telecommunication services over the physical infrastructure of the traditional network operator, bypassing the lengthy and costly development cycle involved in offering carrier grade communication services. To adapt to this new landscape, the IP Multimedia Subsystem (IMS) was proposed. Its ongoing standardisation is being led by the 3rd Generation Partnership Project (3GPP) and it is a Next Generation Network (NGN) that is heading towards converged multimedia services. This NGN contains IP based network services that allow telecommunication operators the reuse of common building blocks for new services, reducing the time and cost to provision a new service. The thesis begins with an overview of the current landscape that plays a critical role in the formation and deployment of the IMS. This is followed by a literature review of service provisioning in the IMS. It looks at both the current, standardised architecture as well as several new approaches currently being researched. It determines that there is a need for further work in this area, and this concurs with the view of the standards body responsible for the IMS. However, there are limits on what can be proposed moving forward as deployment of the IMS architecture has already begun. The work continues with the creation of a novel architecture that would allow a network operator greater flexibility in routing service requests, as well as the ability to expose this functionality to the end user. This allows the end user to customise their service usage, something which is in great demand with the rise of user generated content and the new services being used over the internet. A prototype of the architecture is evaluated to determine the feasibility of the proposed architecture. Emphasis is placed on ensuring correct operation and increasing the range of functionality available. The prototype is evaluated in a test-bed provisioned through the use of Amazon's Elastic Compute Cloud (EC2). This is an Infrastructure as a Service (IaaS) offering that provides resizeable or elastic computing resources to researchers or developers, allowing the rapid deployment and reconfiguration of many different virtual servers. Different combinations of services that were identified as not being possible under the previous standardised architecture are evaluated in this test-bed. The proof of concept implementation provides the necessary functionality to execute these service combinations successfully without adding custom combined services. The evaluation is comprised of both functional and performance tests although the emphasis is on the former. As all components have been made available under open source licenses, it is possible for other researchers to reproduce this work and continue investigating this area. The work successfully demonstrates improved service triggering in the IMS whilst providing end users a much higher degree of control over the use of their telecommunication services.